Longitudinal phase 2 clinical trials of live, attenuated tularemia vaccine in healthy research laboratory workers - Saunders, David L.; Pierson, Benjamin C.; Haller, Jeannine; Norris, Sarah; Cardile, Anthony P.; Reisler, Ronald B.; Okwesili, Arthur C.; Boudreau, Ellen; Rusnak, Janice; Danner, Denise K.; Purcell, Bret K.; Barth, James F.; et al. (Frontiers in Bacteriology, 2024)
Background: Tularemia is caused by the intracellular bacterium Francisella tularensis (Ft). It was weaponized historically due to low infectious aerosol dose, high morbidity and mortality rates for pneumonic disease. The US Army developed the attenuated Live Vaccine Strain (LVS) from stocks provided by the former Soviet Union in the 1950s. The vaccine has been safe and immunogenic over the ensuing decades in numerous clinical trials including human challenge studies. Methods: Two sequential FDA-regulated, non-randomized, single arm LVS trials enrolled at-risk laboratory personnel working on tularemia in bio-containment laboratories under IND#157. Volunteers received a single dose of LVS manufactured in 1962 by scarification. Positive immunization was based on local scarification site ‘take reaction’, and either a >1:20 tularemia antigen microagglutination (MA) titer (protocol FY03-24; 2004-8) or greater than 4-fold rise in MA titer (protocol FY07-15; 2009-2017). Those still negative by week 4 were offered a second dose. Results: The LVS vaccine was safe, well tolerated and highly immunogenic. Between the two studies, all recipients (100%) had positive ‘take reactions’, with 95.5% of those in study FY03-24 having a positive response following initial vaccination. All but 3 subjects (98%) in protocol FY03-24 had positive MA titer results defined as >1:20, most within 28-35 days. In protocol FY07-15, 95% of subjects had a 4-fold or greater rise in MA titer, the primary immunogenicity endpoint for that study. Discussion: LVS vaccine administered to laboratory workers at risk for tularemia exposure over 12 years was safe and highly immunogenic. Response rates remained robust despite the vaccine lots employed having been manufactured 42-55 years prior to vaccination. The results as well as historical comparator data presented here serve as a benchmark for future studies. LVS remains unlicensed due to instability in culture and the potential for reversion to the wild-type pathogen. Despite the threat, there are no FDA-approved vaccines. . In the absence of a clinical-stage commercial development effort, an ongoing LVS vaccine protocol under investigational new drug (IND) application for at-risk laboratory workers to prevent occupationally-acquired disease should be considered based on extensive favorable data for this vaccine.